Progressive insights into fibrosarcoma diagnosis and treatment: leveraging fusion genes for advancements - Tang, Xiaodi; Hu, Xin; Wen, Yang; Min, Li (Frontiers in Cell and Developmental Biology, 2023)
Fibrosarcoma, originating from fibroblast cells, represents a malignant neoplasm that can manifest across all genders and age groups. Fusion genes are notably prevalent within the landscape of human cancers, particularly within the subtypes of fibrosarcoma, where they exert substantial driving forces in tumorigenesis. Many fusion genes underlie the pathogenic mechanisms triggering the onset of this disease. Moreover, a close association emerges between the spectrum of fusion gene types and the phenotypic expression of fibrosarcoma, endowing fusion genes not only as promising diagnostic indicators for fibrosarcoma but also as pivotal foundations for its subcategorization. Concurrently, an increasing number of chimeric proteins encoded by fusion genes have been substantiated as specific targets for treating fibrosarcoma, consequently significantly enhancing patient prognoses. This review comprehensively delineates the mechanisms behind fusion gene formation in fibrosarcoma, the lineage of fusion genes, methodologies employed in detecting fusion genes within fibrosarcoma, and the prospects of targeted therapeutic interventions driven by fusion genes within the fibrosarcoma domain.